Disrupting Deportability : Transnational Workers Organize - Vosko, Leah F. (Book collections on Project MUSE., 2019)
"Explores the effects of deportability--a social condition characterized by the possibility of removal--on the exercise of labor rights amongst temporary migrant workers--primarily Mexican nationals engaged in Canada's model Seasonal Agricultural Worker Program (SAWP)--struggling to organize, bargain collectively and sustain bargaining units"--